Pattern change and ecological risk analysis of Shilin World Geopark landscape - Shi, Yiqi; Gao, Hongxia; Tan, Shucheng; Qin, Hongfu; Tian, Zhuang; Meng, Jingxian; Zheng, Xin (Frontiers in Ecology and Evolution, 2024)
This study considered Shilin World Geopark as the research object and constructed a landscape ecological risk assessment model based on the landscape pattern index by using remote sensing image data during five periods between 2000 and 2020. In addition, it analyzed the spatial and temporal changes of landscape ecological risk in the region. Spatial autocorrelation analysis was utilized to study spatial differences in the landscape ecological risk in the park. The results showed that during the study period, (1) cultivated land, forest land, and rocky desertification land were the main landscape types, different landscape types differed, and the area of rocky desertification land and building land increased by 37.47 km2 and 14.29 km2, respectively, while the area of cultivated land and grassland decreased significantly, with changes of 34.11 km2 and 18.67 km2; (2) landscape ecological risk of the park showed significant spatial differences, the ‘high–high’ risk areas have been concentrated mainly in the central and northern parts of the park, the ‘low–low’ risk areas have been concentrated in the central part and the southwest-southeast area of the park; and (3) landscape ecological risk of the geopark has been increasing, with the degree of landscape ecological risk being spatially positively correlated. The results of the study are of great significance for maintaining ecosystem health of the Shilin World Geopark and optimizing the ecological risk management of the park.